A A Comprehensive Review of Student’s Perceptions Towards Learning Speaking Skills in Secondary Education - Nadia Pega; Tasya Alkhaira; Hermalia; Afri Astarina; Erwin Pohan (EDUJ : English Education Journal, 2025)
This review explores secondary school students' perceptions of learning speaking skills, emphasizing the importance of effective communication in both academic and real-world settings. While speaking, especially in a second language, is crucial, many students face challenges such as anxiety and lack of confidence. Understanding these perceptions is essential for educators to enhance teaching strategies and create supportive environments. The study explores factors influencing students' views, including motivation, teaching methods, and the learning environment. Motivated students tend to be more confident and engaged in speaking activities, while interactive methods, such as group activities and technology integration, improve participation. A positive and inclusive classroom atmosphere can reduce fear and promote confidence. However, challenges like fear of mistakes and limited vocabulary persist, requiring adaptive teaching techniques focused on gradual skill development and constructive feedback. The study recommends innovative approaches, such as task-based learning and gamified exercises, to make speaking practice enjoyable and effective. The findings provide valuable insights for improving English language education and suggest areas for future research, including cultural influences and technological advancements. Keywords: Student perceptions; speaking skills; secondary education; learning strategies; language proficiency; communication skills.